Implementation Drivers of County Integrated Strategic Plans and Growth of Small and Medium Enterprises in Busia County, Kenya - Kwamini, Nelson Makokha (JOOUST, 2022)
Small and Medium Enterprises (SMEs) play a significant role in development of any economic growth. Economies have increasingly employed SMEs as a framework to achieve economic performance in a more efficient manner. Despite the crucial role, SMEs are affected by several factors such as leadership, planning, resources among others. Studies point out that 90% of strategic initiatives fail, due to implementation difficulties. Failure in implementation of strategy causes huge costs in the organization. Despite the significance of strategy implementation process in strategic management, it is often eclipsed by a focus on other dimensions of strategy. Strategic planning and implementation are important for SMEs to be able to face local and global competition, technological changes, and cope with increased dynamics in the markets. Studies reveal varied conceptualizations of key drivers of strategy implementation. The general objective of this study was to determine the effect of implementation drivers of county integrated development plans and growth of SMEs in Busia County. Specific objectives were; to determine the effect of: organizational culture, leadership, ICT and resource allocation as strategy implementation drivers on growth SMEs. The study was guided by, stakeholder theory, Resource Based View theory, Enterprise Life Cycle Model and Okumu’s Strategy Implementation Framework. The study employed mixed methods design where explanatory, correlation and survey research designs were adopted. Both stratified and simple random sampling techniques were used to pick 386 respondents from a target population of 11296 SMEs owners. Data was collected using questionnaires. Data was cleaned, coded, and analyzed using descriptive and inferential statistics aided by SPSS. The findings revealed that culture had a positive and significant effect on growth of SMEs (β= .107; p<.05); leadership had a positive and significant effect on growth of SMEs (β= .142; p<.05), information communication technology had a negative and insignificant effect on growth of SMEs (β= -0.024; p>.05) and allocation of resources had a positive and significant effect on growth of SMEs (β= .324; p<.05).Given that different County Governments have different resources in terms of economic activities and business opportunities it is recommended that a similar study could be done to evaluate the effect of leadership, culture, resource allocation and information communication technology on growth and performance of SMEs by application of panel data techniques.